MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA MAN 1 ACEH TIMUR - RUSMIATI RUSMIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Writing an exposition text has not yet obtained the maximum score according to the minimum completeness criteria of the school. So we need a method to make it easier for students, namely mind mapping. Obtaining the results of increasing the ability to write expository texts through mind mapping is the goal of the research. MAN 1 Aceh Timur became the research site. A total of 18 students of class X MIA 1 in the academic year 2021/2022 became the subjects of the research. Classroom Action Research (CAR) is a research design through four research steps, namely planning (plan), action (action), observation (observation) and reflection through two cycles. Tests and observations become instruments in research. Data analysis was carried out through a qualitative approach by calculating the class average value using the classical completeness percentage. Students who get a KKM score of 75 are declared complete. The results showed that the ability to write expository texts through mind mapping at MAN 1 Aceh Timur in the first cycle was 55.55%% or 10 students in the poor category. Meanwhile, after being given the second cycle, the results showed 100% or 18 students. Based on the results of the study, it was concluded that students' ability to write expository texts through mind mapping could increase. ABSTRAKMenulis teks eksposisi belum memperoleh nilai yang maksimal sesuai dengan kriteria ketuntasan minimal sekolah. Sehingga diperlukan suatu metode untuk memudahkan siswa yaitu dengan mind mapping. Memperoleh hasil peningkatan kemampuan menulis teks eksposisi melalui mind mapping merupakan tujuan dari penelitian. MAN 1 Aceh Timur menjadi tempat penelitian. Sebanyak 18 siswa kelas X MIA 1 pada tahun ajaran 2021/2022 menjadi subjek dalam penelitian. Penelitian Tindakan Kelas (PTK) merupakan desain penelitian melalui empat langkah penelitian yaitu perencanaan (plan), Tindakan (action), pengamatan (observasi) dan refleksi melalui dua siklus. Tes dan observasi menjadi instrument dalam penelitian. Analisis data dilakukan melalui pendekatan kualitatif dengan menghitung nilai rata-rata kelas menggunakan persentase ketuntasan secara klasikal. Siswa yang mendapatkan nilai KKM ?75 dinyatakan tuntas. Hasil penelitian menunjukkan kemampuan menulis teks eksposisi melalului mind mapping di MAN 1 Aceh Timur pada siklus I sebesar 55,55%% atau 10 siswa dengan kategori kurang. Sedangkan setelah diberikan siklus II menunjukkan hasil sebesar 100% atau 18 siswa. Berdasarkan hasil penelitian disimpulkan kemampuan siswa dalam menulis teks eksposisi melalui mind mapping dapat meningkat.